2006
DOI: 10.1029/2006ja011688
|View full text |Cite
|
Sign up to set email alerts
|

Digisonde spread F and GPS phase fluctuations in the equatorial ionosphere during solar maximum

Abstract: [1] The Jicamarca (11.95°S, 76.87°W) digisonde and the Arequipa (16.47°S, 71.49°W) GPS receiver observed the equatorial F region irregularities on the western South America from April 1999 to March 2000. The spread F measured by the digisonde were classified into four types, and the GPS phase fluctuations derived from the temporal variation of total electron content were divided into three levels to represent the irregularity strength. The observation shows that the occurrences of all four types of spread F ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
9
35
1
Order By: Relevance
“…These four types of SF were first classified in 2006 in COSPAR meeting at Beijing. At the same time, Chen et al (2006) have also reported their four types of SF (Fig. 2 in their paper) observed by digisonde at Jicamacar, named as FSF-I, RSF-I, FSF-II, and RSF-II, which are the same as the FSF, RSF, MSF, and SSF, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These four types of SF were first classified in 2006 in COSPAR meeting at Beijing. At the same time, Chen et al (2006) have also reported their four types of SF (Fig. 2 in their paper) observed by digisonde at Jicamacar, named as FSF-I, RSF-I, FSF-II, and RSF-II, which are the same as the FSF, RSF, MSF, and SSF, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…The ESF is often associated with plasma bubbles, produced by the generalized Rayleigh-Taylor (GRT) instability which includes cross electric field instability, neutral wind effects and various drift mode instabilities (e.g., Dungey, 1956;Kelley, 1989;Sultan, 1996). ESF observations have been made through a variety of instruments over low and middle latitudes, such as ground-based ionosondes, Incoherent Scatter Radar, satellite borne topside sounders and in-situ measurements (Fejer and Kelley, 1980;Basu and Basu, 1985;Chandra, 1990;Mathews et al, 2001;Chen et al, 2006;Bhaneja et al, 2009). Their morphological characteristics at different longitudes of equatorial latitudes has been described as a function of spatial, temporal, solar cycle and magnetic activity variations (Aarons, 1993;Abdu et al, 1981Abdu et al, , 1985Abdu et al, , 1992Cragin et al, 1985;Kil and Heelis, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since scintillation studies are essential for developing forecasting models, it is very important to improve our knowledge of the behavior of the irregularities that cause scintillations. The spreading echo is usually categorized into Correspondence to: M. Pezzopane (michael.pezzopane@ingv.it) two main types, the RSF and the frequency spread-F (FSF) (Piggott and Rawer, 1972), even though several authors perform further subdivisions into RSF-I, RSF-II, FSF-I, and FSF-II (Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hysell et al, 1990;Rodrigues et al, 2008), ground-based GPS receiver (e.g. Pi et al, 1997;Chen et al, 2006), satellite GPS receiver (e.g. Straus et al, 2003), in-situ satellite probe (e.g.…”
Section: Introductionmentioning
confidence: 99%